Vergangenheitsverhältnisse: Ein Korrektiv zum Paradigma des »kollektiven Gedächtnisses« mittels Walter Benjamins Erfahrungstheorie - Denschlag, Felix (transcript, 2017)
The theory of "collective memory" and its idea of identity is critically analyzed and complemented by means of Walter Benjamin's theory.